2023
DOI: 10.1039/d3ta02209a
|View full text |Cite
|
Sign up to set email alerts
|

Multifunctional molecule interface modification for high-performance inverted wide-bandgap perovskite cells and modules

Abstract: Wide-bandgap (≥1.66 eV) inverted perovskite solar cells (PSCs) are important portions of tandem silicon/PSCs. But the poor efficiency and phase stability are still unresolved and blocking the industrialization of the...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 47 publications
0
10
0
Order By: Relevance
“…The processes for fabricating the device with a configuration of ITO/MeO-2PACz/Cs 0.05 (FA 0.77 MA 0.23 ) 0.95 Pb­(I 0.70 Br 0.30 ) 3 /C 60 /BCP/Ag are similar to the previously published work, except that we used a 0.5 mg·mL –1 MeO-2PACz solution and a mixture solution of 0.05 mmol of CsI, 1.09 mmol of FAI, 0.32 mmol of MABr, 0.99 mmol of PbI 2 , and 0.50 mmol of PbBr 2 in 200 μL of DMSO and 800 μL of DMF. The antisolvent is 200 μL CB.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The processes for fabricating the device with a configuration of ITO/MeO-2PACz/Cs 0.05 (FA 0.77 MA 0.23 ) 0.95 Pb­(I 0.70 Br 0.30 ) 3 /C 60 /BCP/Ag are similar to the previously published work, except that we used a 0.5 mg·mL –1 MeO-2PACz solution and a mixture solution of 0.05 mmol of CsI, 1.09 mmol of FAI, 0.32 mmol of MABr, 0.99 mmol of PbI 2 , and 0.50 mmol of PbBr 2 in 200 μL of DMSO and 800 μL of DMF. The antisolvent is 200 μL CB.…”
Section: Methodsmentioning
confidence: 99%
“…The PSC they manufactured achieved a PCE of 21.82% for the 1.67 eV bandgap inverted PSCs. 25 Here, we designed and synthesized 1,2,4-tris(3-thienyl)benzene (THB). Due to its appropriate size, S atoms in THB can strongly interact with Pb 2+ on the surface of the WBG perovskite to the maximum extent, and THB effectively passivates surface defects and inhibits the recombination of carriers caused by these defects.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They suggested that PI modifies the surface by reducing the excess lead iodide in the perovskite and penetrates the bulk perovskite films. This modification led to WBG PSCs achieving a V oc of 1.36 V, reaching 90% of the radiative limit [83] . Wang et al used a multifunctional molecule, pyridinyl-benzimidazolium chloride (MHI), to stabilize the perovskite surface.…”
Section: Modification Of Upper Interface In Inverted Wbg Pscsmentioning
confidence: 99%
“…Molecule regulation is often used to manipulate Pb-related defects in a perovskite with functional O, S, and P atoms to donate the lone pair of electrons to Pb 2+ ions. 18–22 As a typical molecule, crown ether has been recognized as modifiers or stabilizers in PSCs with a unique ring structure and abundant oxygen chelating with Pb 2+ ions 23–28 to improve the efficiency and stability. Despite the enhancement by crown ethers, most of the devices still suffer from large V oc deficit and unsatisfactory PCE values.…”
Section: Introductionmentioning
confidence: 99%